PENGARUH KONEKSI POLITIK DAN FAKTOR-FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Monica Citra Listyaningrum; Rutji Satwiko (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to examine the effect of political connections, leverage, profitability, sales growth, transfer pricing, executive characteristics, and capital intensity on tax avoidance. The population of this research is all manufactured companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2021. This research sample was obtained using a purposive sampling method that produced 60 companies that met all the criteria, so that 180 data were obtained which were used as research samples. The source of the data used in this research was obtained from the website of the Indonesia Stock Exchange. Hypothesis testing in this study was carried out using multiple regression models. Empirical evidence concludes that leverage and profitability affect tax avoidance whereas political connections, sales growth, transfer pricing, executive characteristics, and capital intensity have no influence on tax avoidance